Penerapan Etika Bisnis dalam Pasar Tradisional Berdasarkan Perspektif Islam : Implementation of Business Ethics in Traditional Markets Based on Islamic Perspective - Salmalia Hera Dewinta; Hanifatu Sadiyyah; Afifah Alfina Ramadhani; Zelinandita Asti Utami; Hanifa Rahma Ika; Ahmad 'Uroidhi (Litera Academica Publishing, 2024)
This research aims to analyse business ethics in traditional markets based on an Islamic perspective. In traditional markets, the interaction between sellers and buyers involves not only economic transactions, but also social and cultural values that have existed for a long time. Therefore, business ethics become very important to maintain trust and good relations between market participants. Good business ethics not only contribute to the sustainability of the business, but also create a healthy and sustainable environment for society. The research method used in this study is a literature study, which aims to collect, analyse and synthesise relevant information regarding business ethics in traditional markets from an Islamic perspective. The results show that the fundamental foundation of Islamic business ethics is firmly embedded in the teachings of the Quran and the Hadith of the Prophet Muhammad, which do not merely provide transactional guidelines, but rather create a moral paradigm in every trading activity. In traditional markets, there are several main principles that become the moral compass for Muslim traders, namely honesty, fairness, transparency and mutual respect. One example of a case that applies Islamic business ethics is in Beringharjo market vegetable traders. The positive impact of implementing business ethics also contributes to the creation of a healthier and more sustainable market environment. When traders respect each other's prices and quality of goods, the competition becomes fairer. This encourages traders to continuously improve the quality of their products and services, so that consumers get better value.